Lifestyle profile of patients with chronic renal disease in hemodialysis - Santos, Telma Suanne Rocha dos (2021)
This study aimed to evaluate the lifestyle profile of patients with chronic kidney disease undergoing hemodialysis. This was a quantitative, cross-sectional, analytical and descriptive study. Data were collected at Baixo Amazonas Regional Hospital, in the municipality of Santarém, state of Pará. The participants answered a sociodemographic, associated factors questionnaire created by the authors, and for lifestyle analysis, the Individual Lifestyle Profile Instrument was used. Seventy chronic kidney patients, predominantly male and aged between 21 and 71 years, were evaluated. The average score of the global lifestyle questionnaire was 20.8 ± 7 points, 15.7% had a negative lifestyle rating, 72.2% regular and 8.5% positive. For 24.2%, the disease has an important impact on life. There was a prevalence of regular lifestyle, as well as self-report of important impact of chronic kidney disease on the patient’s life, which can potentially be mitigated by components of a health-promoting lifestyle.